Image, Imagination, Magic, Imaginary: Contemporary Experience and Cognition - Basbaum, Sérgio Roclaw [UNESP] (Springer Nature, 2023)
In contemporary global digital cultureCulture, digital, the production and consumption of imagesImage have reached unprecedented levels, with billions of imagesImage being made and seen in so-called social networksNetwork and other media every day. This essay intends to approachApproach this question through a reductionist version of the concepts of (a) imageImage and (b) imaginationImagination in order to derive (c) a notion of imaginaryImaginary. Then, we address (d) their impact on human cognitionCognition, the way an increasing imaginaryImaginary zone modulates our actionsAction and decisionsDecision. Through an interdisciplinary dialogue with several authors from different fields, from philosophy to artArt and scienceScience, we suggest that contemporary challenges such as the fake-newsNews phenomenon are better understood through a deeper comprehensionComprehension of our relation to imagesImage and their impact on human consciousnessConsciousness. “Image”, imaginationImagination, magicMagic, imaginaryImaginary. (Adapted with permission from the Association of ScienceScience and ArtArt (ASA), Universal Scientific EducationEducation and ResearchResearchNetworkNetwork (USERN); Made by Fateme Ghorbannezhad).
Keywords: Digital culture; Enactive cognition; Image; Imaginary; Imagination; Interpretation of images